Bacteria may induce the secretion of mucin‐like proteins by the diatom Phaeodactylum tricornutum. Issue 3 (9th May 2016) - Buhmann, Matthias T.; Schulze, Birgit; Förderer, Alexander; Schleheck, David; Kroth, Peter G.
Abstract : Benthic diatoms live in photoautotrophic/heterotrophic biofilm communities embedded in a matrix of secreted extracellular polymeric substances. Closely associated bacteria influence their growth, aggregation, and secretion of exopolymers. We have studied a diatom/bacteria model community, in which a marine Roseobacter strain is able to grow with secreted diatom exopolymers as a sole source of carbon. The strain influences the aggregation of Phaeodactylum tricornutum by inducing a morphotypic transition from planktonic, fusiform cells to benthic, oval cells. Analysis of the extracellular soluble proteome of P. tricornutum in the presence and absence of bacteria revealed constitutively expressed newly identified proteins with mucin‐like domains that appear to be typical for extracellular diatom proteins. In contrast to mucins, the proline‐, serine‐, threonine‐rich (PST) domains in these proteins were also found in combination with protease‐, glucosidase‐ and leucine‐rich repeat‐domains. Bioinformatic functional predictions indicate that several of these newly identified diatom‐specific proteins may be involved in algal defense, intercellular signaling, and aggregation.